Kontribusi Pembiayaan Bank Syariah Dalam Pengembangan Usaha Mikro (Studi pada Bank Aceh Syariah KCP Lam Ateuk, Kecamatan Kuta Baro, Aceh Besar) - Jalilah, Jalilah; Arifin, Muhammad (Program Studi Perbankan Syariah FEBI UIN Ar-Raniry, 2025)
Micro, Small, and Medium Enterprises (MSMEs) constitute a strategic sector that plays a pivotal role in fostering economic growth. Despite their significance, this sector encounters numerous challenges, particularly in accessing adequate capital. Financing through the banking sector has therefore emerged as a viable solution to address these challenges. This study aims to analyze the contribution of microfinancing provided by Bank Aceh Syariah KCP Lam Ateuk in fostering the development of its clients' businesses. The research employs a qualitative descriptive methodology, drawing on data collected through interviews and documentation. The findings reveal that financing from Bank Aceh Syariah exerts a positive influence on the growth of micro-enterprises. This influence is evident through the provision of business capital, capacity-building initiatives such as education and training, as well as ongoing supervision. These efforts collectively contribute to increased income levels and business advancements among micro-entrepreneurs supported by Bank Aceh Syariah within the region.The insights from this study are intended to serve as a valuable reference for Islamic financial institutions, particularly Islamic banks, in their endeavor to optimize financing distribution and foster the development of the MSME sector. The study emphasizes the importance of comprehensive business mentoring to ensure that financing is allocated efficiently, thereby enhancing the productivity and sustainability of MSMEs.